The Rise of China in Sub-Saharan Africa: its Ambiguous Economic Impacts - (:unkn) unknown (My University, 2011)
The paper analyses the economic relationships between China and Sub-Saharan African countries, including original contractual relationships that link exports from Sub-Saharan Africa to China and investment by Chinese firms in Sub-Saharan Africa. Unlike the 'traditional' partners of Sub-Saharan African economies (European countries, USA), these relations inextricably combine trade, aid and investment, which may create 'lock-in' effects. China's trade and investment focus on the commodities that are produced by African countries, which are crucial inputs in China's growth, with the risk of a growing dependence of African economies on the exports of raw materials and the negative effects that are associated with such dependence, especially in oil-exporting countries. Chinese investment, however, increasingly involves other sectors, such as the manufacturing sector. In addition, Chinese investment and aid have positive effects, such as the improvement of infrastructure, the lack of which being one of the key factors of the stagnation of African economies. The rise of China in Sub-Saharan Africa also implies significant additional resources and a welcome increase in the number of 'players'. The article thus shows the ambivalence of the impacts of China, which moreover substantially vary according to countries' export structure and the nature of their political institutions.
Keywords: African Research